2009
DOI: 10.4315/0362-028x-72.9.1916
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Iceberg Lettuce by Titanium Dioxide–UV Photocatalytic Reaction

Abstract: Securing the physical quality and microbial safety of fresh foods has been a major focus in the food industry. To improve quality and increase the shelf life of fresh produce, disinfection methods have been developed. Titanium dioxide (TiO2) photocatalytic reactions under UV radiation produce hydroxyl radicals that can be used for disinfection of foodborne pathogenic bacteria. We investigated the effects of TiO2-UV photocatalytic disinfection on the shelf life of iceberg lettuce. Counts of natural microflora (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…So far, the only studies about TiO 2 NPs and L. monocytogenes concerned the photocatalytic activity of TiO 2 NPs against bacteria, as alternative means of disinfecting surfaces or food contaminated by planktonic or biofilm bacteria [24] [25] [26] [27]. Since no data yet are available on the effects of non UV-irradiated TiO 2 nanoparticles on listeria cells, the aim of present study was to explore interaction between bacteria and nano-sized TiO 2 , with special focus on biofilm formation and CaCo-2 cell colonization.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the only studies about TiO 2 NPs and L. monocytogenes concerned the photocatalytic activity of TiO 2 NPs against bacteria, as alternative means of disinfecting surfaces or food contaminated by planktonic or biofilm bacteria [24] [25] [26] [27]. Since no data yet are available on the effects of non UV-irradiated TiO 2 nanoparticles on listeria cells, the aim of present study was to explore interaction between bacteria and nano-sized TiO 2 , with special focus on biofilm formation and CaCo-2 cell colonization.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al . () reported that TUVP processing reduced counts of natural microflora and inoculated pathogenic bacteria on iceberg lettuce immediately after treatment, as well as during storage at different temperatures, and prolonged the product shelf life. Gündüz et al .…”
Section: Resultsmentioning
confidence: 99%
“…a) following a previous study (Kim et al . ). The reactor consisted of a stainless steel vessel (30 l), an air pump and six UVC lamps (254 nm, 35 W, 25 mW cm −2 , Sankyo Denki, Tokyo, Japan) in TiO 2 ‐coated quartz tubes (38 cm length, 24·5 mm outer diameter, TiO 2 coating thickness 0·7–0·9 mm; Taekyeong UV Co., Namyangju, South Korea).…”
Section: Methodsmentioning
confidence: 97%
“…The use of chlorinated water that may be insufficient for inactivation of all bacterial pathogens can cause health hazards due to generation of trihalomethanes (Kim et al . , ) and can also result in undesirable by‐products and, at the same time, create disposal problems. Treated products may also require water rinsing before use to remove residual chlorine.…”
Section: Introductionmentioning
confidence: 99%